Effect of dietary methionine level on productivity and carcass characteristics of ross 308 broiler chickens - Paledi, Mashego Queen (My University, 2019)
Two experiments were conducted to determine the effect of dietary methionine level on productivity and carcass characteristics of Ross 308 broiler chickens. In each experiment, the diets were isocaloric and isonitrogenous but with different dietary methionine levels. Five diets were formulated to contain dietary methionine levels of 4, 5, 6, 8 or 9g/kg DM. The first experiment commenced with 300 unsexed Ross 308 broiler chickens with initial average live weights of 42 ± 2g per chicken. The chickens were randomly assigned to five treatments with five replications, resulting in 25-floor pens with 12 chickens per replicate. The second experiment commenced with 150 male Ross 308 broiler chickens with initial average live weight of 637 ± 12g per chicken. The chickens were randomly assigned to five treatments with three replications, resulting in 15-floor pens with 10 chickens per replicate. A complete randomized design was used in each experiment. Data was analysed using the General Linear Model (GLM) procedures of the statistical analysis of variance, Version 9.3.1 software program. Where there were significant differences, mean separation was done using the Tukey test at the 5% level of significance. A quadratic regression model was used to determine the optimal productivity of the chickens while a linear model was used to determine the relationships between dietary methionine level and responses by the chickens in the variables measured. The treatments for the first experiment were UM4 (4g methionine/kg DM), UM5 (5g methionine/kg DM), UM6 (6g methionine/kg DM), UM8 (8g methionine/kg DM) and UM9 (9g methionine/kg DM). Feed intake, growth rate, feed conversion ratio (FCR), metabolisable energy intake and nitrogen retention of unsexed Ross 308 broiler chickens aged one to 21 days were not affected (P>0.05) by dietary methionine level. Similarly, dietary methionine level did not have any effect (P>0.05) on diet crude protein (CP), acid detergent fibre (ADF), neutral detergent fibre (NDF) and fat digestibilities in unsexed Ross 308 broiler chickens aged 14 to 21 days. Dietary methionine level did not have any effect on live weights of broiler chickens at 21 days. Live weights of unsexed Ross 308 broiler chickens aged 7 or 14 days were not improved (P>0.05) by increasing dietary methionine level from 4 to 9g/kg DM. Crop, gizzard and small intestine weights and crop, proventriculus and gizzard digesta pH values of unsexed Ross 308 broiler chickens aged 21 days were not affected v (P>0.05) by dietary methionine level. Similarly, dietary methionine level did not improve (P>0.05) caecum and large intestine lengths of unsexed Ross 308 broiler chickens aged 21 days. However, dietary methionine level affected (P<0.05) dry matter (DM) and ash digestibilities of unsexed Ross 308 broiler chickens aged 14 to 21 days. Proventriculus and large intestine weights, gastrointestinal tract and small intestine lengths of unsexed Ross 308 broiler chickens aged 21 days were improved (P<0.05) by increasing dietary methionine level. In addition, increasing dietary methionine level increased (P<0.05) small and large intestine digesta pH values of broiler chickens aged 21 days. Thus, dry matter digestibility, live weights at day 7 ad 14, caecum length, large intestine length and digesta pH were optimized at different dietary methionine levels of 7.26, 5.29, 4.99, 6.80, 4.84 and 6.37g/kg DM feed, respectively. The treatments for the second experiment were MM4 (4g methionine/kg DM), MM5 (5g methionine/kg DM), MM6 (6g methionine/kg DM), MM8 (8g methionine/kg DM) and MM9 (9g methionine/kg DM). Dietary methionine level did not have effect (P>0.05) on feed intake of male Ross 308 broiler chickens aged 6 weeks. However, dietary methionine level improved (P<0.05) feed intake of male Ross 308 broiler chickens aged 4 or 5 weeks. Live weights of male Ross 308 broiler chickens aged 28 days were not affected (P>0.05) by dietary methionine level. However, live weights of male Ross 308 broiler chickens aged 35 and 42 days were affected (P<0.05) by dietary methionine level. Similarly, dietary methionine level affected (P<0.05) DM, CP, ADF, NDF, fat and ash digestibilities of male Ross 308 broiler chickens aged 35 to 42 days. Thus, dietary methionine levels of 6.93, 7.70, 6.85 and 11.27g/kg DM optimized dry matter, CP and fat digestibilities, and live weight of male broiler chickens aged 42 days. Dietary methionine level did not affect (P>0.05) FCR, growth rate and metabolisable energy intakes of male Ross 308 broiler chickens. Increasing dietary methionine level from 4 to 9g/kg DM improved (P<0.05) nitrogen retention of male Ross 308 broiler chickens aged 22 to 42 days. Dietary methionine level did not have any effect (P>0.05) on proventriculus, gizzard, caecum and large intestine weights, caecum, small and large intestine lengths, and crop, gizzard, caecum and large intestine digesta pH values of male Ross 308 broiler chickens aged 42 days. Crop and small vi intestine weights and gastrointestinal tract lengths of male Ross 308 broiler chickens aged 42 days were improved (P<0.05) by dietary methionine level. Similarly, dietary methionine level affected (P<0.05) proventriculus and small intestine digesta pH values of male Ross 308 broiler chickens aged 42 days. Thus, dietary methionine levels of 6.558 and 7.851g/kg DM optimized broiler chicken crop weight and GIT length. Dietary methionine level affected (P<0.05) carcass organ weights of male Ross 308 broiler chickens aged 42 days. Increasing dietary methionine level increased chicken breast meat weight. However, there was no clear trend for the other carcass organs. Meat flavour and shear force values of male Ross 308 broiler chickens aged 42 days were not affected (P>0.05) by dietary methionine level. However, dietary methionine level affected meat tenderness and juiciness. Thus, dietary methionine levels of 10.09 and 13.32g/kg DM optimized broiler chicken meat tenderness and juiciness. .
Thesis (M. Sc. Agriculture (Animal Production)) -- University of Limpopo, 2019
Keywords: Dietary methionine level; Ross 308 broiler chickens; Feed intake; Growth rate; Live weights; Carcass characteristics; Broilers (Chickens); Broilers (Chickens) -- Productivity; Poultry -- Feeding and feeds